Optical features and thermal properties of charged AdS Euler–Heisenberg black hole surrounded by perfect fluid dark matter - M. R. Shahzad; G. Abbas; Tao Zhu; R. H. Ali; Asifa Ashraf; Badr S. Al-Kahtani (European Physical Journal C: Particles and Fields)
Abstract In this article, motivated by the high interest in Euler–Heisenberg nonlinear electrodynamic theory, we investigated several thermal aspects of the charged Euler–Heisenberg black hole surrounded by perfect fluid dark matter. To ensure the validity of the first law of thermodynamics, we measured the conserved thermal quantities. Furthermore, the local and global thermal stability of the charged Euler–Heisenberg black hole surrounded by perfect fluid dark matter is also discussed in canonical and grand canonical ensembles and reveals how the coupling parameter affects the stability regions. We also examined the extended second-order phase transition via P–V criticality. Finally, we extend our study to the optical features of the charged Euler–Heisenberg black hole surrounded by perfect fluid dark matter, such as the black hole shadow and energy emission rate and observe the impact of the coupling parameter.